When a Judge Becomes More than a Judge: Changes in Local and Regional Administration in the Ming Dynasty as Seen through the Role of the Prefectural Judge. (2nd January 2018) - Nimick, Thomas G.
Abstract : In the Ming, prefectural, judges always had some administrative duties beyond the hearing of cases. As is revealed in a late-Ming handbook for prefectural judges, by the end of the Ming period those additional duties had expanded beyond prefectural boundaries and in many cases had led to prefectural judges serving as assistants to the regional inspector in the evaluation of local and regional officials. This paper traces the development of the role of prefectural judge from the founding of the dynasty in 1368, the expansion of his responsibilities over time, the debates over the changes, and how the support of the regional inspector became such an important role by the early seventeenth century. This account also serves to illustrate how the practice of local and regional administration changed over the course of the Ming dynasty.